Konsumsi Minuman Beralkohol dan Proses Negosiasi Pemakaian Kondom pada Pekerja Seks Perempuan dan Pelanggannya di Denpasar - Sagung Sawitri, Yanri Subronto, Sri Suryawati (Berita Kedokteran Masyarakat (BKM), 2010)
Background: HIV/AIDS prevalence among female sex workers (FSWs) tend to increase, at 1% in 1999 to 17% in 2008. Meanwhile, previous surveys showed the existence of alcohol consumption behavior among FSWs and their clients, which possibly influence the condom negotiation process among them.Objective: To asses the role of alcohol consumption into condom negotiation process among FSWs and their clients.Methods: Design study was cross sectional, involving 190 FSWs from 22 randomly selected clusters in Denpasar. FSWs were interviewed in their workplace using structured questionnaire, on some variables: demographic characteristics, alcohol consumption pattern, partner/clients characters, and condom negotiation process. Alcohol consumption was defining as either FSWs or the client has consumed alcohol before sexual intercourse. Condom negotiation process were build from 6 items of proposition and 5 items of responses, and were divided into effective and poor process. Those variables were analyzed using Chi-square test, followed by Logistic Regression.Results and conclussions: Around 105 (55.3%) FSWs were consumming alcohol, 62.3% started <25 years, 64.8% has been consumming for >1 year, with three majority drinks were bir (95.2%), wine (34.3%), and arack (26.7%). More than half (54.8%) FSWs never drank >6 drinks and 41.3% has never been drunken with their clients. To new clients, alcohol consumption was proven to influence negotiation process scene 2 (PR 1.822, 95%CI 1.220-2.721), while to regular clients this role was potentially significant (PR 1.501, 95%CI 0.932-2.418). Multivariate analysis demonstrated consistent result among new clients, along with condom access but not with regular clients.Keywords: FSWs, alcohol consumption, condom negotiation